Dental caries prevalence among 5- to 15-year-old children from SEAR countries of WHO: A systematic review and meta-analysis - Sonal S Kale; Pradnya Kakodkar; Sahana H Shetiya; S A Rizwan (Wolters Kluwer Medknow Publications, 2019)
Objectives: The aim of this review was to estimate the prevalence of dental caries in children 5-15 years of age in the countries of the South-East Asia Region (SEAR) of World Health Organization (WHO) and to describe the different caries indices used in these population-based studies. Materials and Methods: A systematic search was carried out in two databases from 1st January 2005 to 31st May 2015. Studies were included if they met the predetermined eligibility criteria. Quality assessment was done with eight-item checklist. Meta-analysis was done for 5, 12, 15, and 6-15 years age group using software STATA version 12. Results: The search strategy yielded 265 unique articles of which 36 met the inclusion criteria included for the review. Data were available for only three SEAR countries. The quality of the majority of the studies ranged from moderate to high. Heterogeneity between the studies was high (I2 > 98%). Variation in dental caries prevalence was found among different ages and among different SEAR countries. The most commonly used index for measuring dental caries was the dentition status of the 1997 WHO criteria. Conclusion: Dental caries continues to be a prominent oral health problem among children in the SEAR countries with huge variation in the prevalence across ages and countries. This review results can be used to update the "WHO Oral Health Country/Area Profile Program" for dental caries among children for SEAR.